RANCANGAN BUKU KERJA PENGUATAN PENGETAHUAN TEKNOLOGI BAGI GURU BIOLOGI SMA - Fitri Olvia Rahmi; Evi Suryawati; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Technological Pedagogical and Content Knowledge (TPACK) is a conceptual framework that shows the relationship between three kinds of knowledge needed by the teacher or prospective teacher including technological knowledge, pedagogical knowledge, and content knowledge. This research is a development research that aims to see how the quality of the design workbook strengthening of technology knowledge for high school biology teacher. This workbook was developed from the essential indicator of Teacher Competency Test (UKG). The design phase, internal validation and trial I are conducted on biology education University of Riau. External validation and trial II are conducted at MGMP Biology Pekanbaru. The quality of workbooks is assessed from four aspects: format and graphics, illustrations, language and content. The workbook generated in this study for the validation stage by five validator validator in whole aspect is in very valid category with score 3.42 and the average value of response of 20 teachers to the workbook developed is 3.53 with very good category, so the workbook deserves to be used as a self-learning resource for strengthening technological knowledge for high school biology teachers.Keywords: Workbook, Technological Knowledge, Senior High School Biology Teacher